2008
DOI: 10.1136/jcp.2007.049049
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of the presence of giant cells in temporal arteritis

Abstract: The presence of giant cells is not a significant factor in determining treatment or clinical progression of temporal arteritis. However, results showed the GC group to have three times the occurrence of blindness and PMR compared to the NGC group. Although the differences were not significant, this analysis suggests an association with giant cells and more aggressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
0
15
0
3
Order By: Relevance
“…Biopsy of the contralateral artery does not add significantly to the diagnostic yield and is therefore not routinely recommended. Overall, available data do not provide convincing evidence that any individual characteristics of the biopsy findings (eg, composition or intensity of the inflammatory infiltrate) are sufficiently predictive for subsequent clinical events to allow guidance of treatment decisions or follow-up in clinical practice 23–35…”
Section: Resultsmentioning
confidence: 99%
“…Biopsy of the contralateral artery does not add significantly to the diagnostic yield and is therefore not routinely recommended. Overall, available data do not provide convincing evidence that any individual characteristics of the biopsy findings (eg, composition or intensity of the inflammatory infiltrate) are sufficiently predictive for subsequent clinical events to allow guidance of treatment decisions or follow-up in clinical practice 23–35…”
Section: Resultsmentioning
confidence: 99%
“…A total of 259 records were identified through electronic searches, and 131 records were extracted from meta‐analysis addressing GCA. The results of the systematic review are shown in Figure ; 34 studies were included (Table ), encompassing 35 arms with GC treatment and totaling 2,505 patients, with a mean age of 69.9 years at diagnosis and 69% women. Inclusions were consecutive in 13 studies (38%) , and 19 studies (56%) were prospective .…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages around the internal elastic membrane are activated by Th1 cells and CD8+ T cells and develop into multinucleated giant cells under the influence of IFNγ . The presence of giant cells was associated with an increased risk of cranial ischemia in 2 studies , and also tended to correlate with more cranial ischemic symptoms in a third study . Macrophages and giant cells near the internal elastic membrane may secrete platelet‐derived growth factor (PDGF) and VEGF, which activate VSMCs .…”
Section: Evidence For Distinct Gca Subsets Based On Immunologic Featuresmentioning
confidence: 99%